Noctilucent finishing coat layer slurry for dry-process veneering of microfiber leather for shoes and product of noctilucent finishing coat layer slurry

By controlling the content of luminous powder in the topcoat layer of the microfiber leather and using a pro-dispersive solvent, the problem of poor mechanical strength caused by the addition of luminous powder is solved, and the ideal optical and mechanical properties of the topcoat layer is achieved.

CN119686131APending Publication Date: 2025-03-25JIANGSU HUAFON MICROFIBRE MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944802.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art causes the problem of poor mechanical strength when adding luminous powder to the topcoat layer of the microfiber leather, especially when the mass concentration of luminous powder is higher than 15%, the performance of the material is significantly reduced.

Method used

By controlling the content of the luminous powder between 18 and 25 wt%, and adding a dispersion-promoting solvent to the polyurethane slurry, the mass ratio and surface tension difference value are adjusted to improve the dispersion stability of the luminous powder and avoid agglomeration problems.

Benefits of technology

The topcoat layer has an ideal initial afterglow brightness and afterglow time, while avoiding the decline in mechanical properties, ensuring that the resulting ultra-fiber leather has a high mechanical strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of microfiber leather, and discloses noctilucent finishing coat layer slurry for dry-process veneering of microfiber leather for shoes and a product thereof, a base material of the noctilucent finishing coat layer slurry for dry-process veneering of microfiber leather for shoes is polyurethane slurry, noctilucent powder is dispersed in the base material, and the polyurethane slurry comprises polyurethane resin and a dispersion promoting solvent; the dispersion promoting solvent is a mixed solvent of an agent A and an agent B; the absolute value of the surface tension difference value of the noctilucent powder in the agent A and the agent B is 3-6mN / m; the base cloth layer, the bonding layer and the noctilucent finishing coat layer are sequentially stacked to obtain the microfiber leather for the shoes. The preparation method of the microfiber leather for the shoes comprises the following steps: firstly coating release paper with noctilucent finishing coat layer slurry to form a finishing coat layer, then coating the surface of the finishing coat layer with bonding layer slurry, combining a microfiber base cloth material on the bonding layer slurry, and separating the release paper after crosslinking, drying and curing to obtain the microfiber leather for the shoes. The microfiber leather disclosed by the invention has excellent light storage performance, and meanwhile, the problem of loss of mechanical strength is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microfiber leather, and relates to a luminous topcoat slurry for dry-process veneer of microfiber leather for shoes and a product thereof. Background Art

[0002] With the rapid development of society, people's demand for leather is growing, and the supply of natural leather can no longer meet this demand. In this context, superfine fiber synthetic leather (abbreviated as superfine leather) came into being. With its unique ability to imitate the three-dimensional structure of natural leather, as well as its excellent feel and physical properties, it has been widely used in many fields. Especially in the field of shoe leather, consumers are no longer satisfied with the basic practical functions of leather, but pursue more diversified special functions, such as luminous effects.

[0003] Microfiber leather has been widely used in the field of shoe leather for its three-dimensional structure and leather-like texture that simulates genuine leather. Microfiber leather is usually composed of a base fabric layer, an adhesive layer and a topcoat layer stacked in sequence, where the base fabric layer provides basic mechanical properties, the adhesive layer achieves the bonding of the topcoat layer and the base fabric layer, and the topcoat layer is responsible for the presentation of surface functionality and appearance.

[0004] Luminous is a phenomenon in which light-storage materials release energy. This phenomenon is achieved by storing the energy of natural light, ultraviolet light and other light sources in light-storage materials and slowly releasing it after the irradiation stops. When luminous materials are applied to the field of synthetic leather, it not only increases the added value of the product, but also meets the market's urgent demand for functional microfiber leather.

[0005] When trying to introduce luminous powder into the topcoat layer, although it can give the microfiber leather the function of storing light and emitting light, it brings about the problem of poor mechanical strength. This is because the existing technology usually requires the addition of a sufficient amount of functional powder to achieve high luminous properties. However, the addition of a large amount of functional powder in the polyurethane resin matrix can easily lead to micro-agglomeration, which will then form stress concentration points inside the tissue, resulting in a significant loss in the mechanical strength of the material. In particular, when the mass concentration of the added powder is as high as 15% or more, it usually has a great impact on the performance of the polyurethane film. When the concentration reaches more than 30%, the film performance is basically lost.

[0006] Therefore, it is of great significance to study a luminous topcoat slurry for dry-process veneer of microfiber leather for shoes and its products to solve the above problems. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and provide a luminous topcoat slurry for dry-process veneer of microfiber leather for shoes and a product thereof.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A luminous topcoat slurry for dry-process veneer of microfiber leather for shoes, wherein the base material is polyurethane slurry, and 18-25wt% of luminous powder is dispersed in the base material;

[0010] The polyurethane slurry comprises a polyurethane resin and a dispersion-promoting solvent, the mass ratio of the polyurethane resin to the dispersion-promoting solvent is 1:4.3-7.7, and the dynamic viscosity of the polyurethane slurry is 3000-15000 cps;

[0011] The dispersibility-promoting solvent is a mixed solvent of agent A and agent B, and the agent A and the agent B are mutually soluble;

[0012] The surface tension of the luminous powder in the agent A is recorded as F1, and the surface tension of the luminous powder in the agent B is recorded as F2. The absolute value of the difference between F1 and F2 is 3 to 6 mN / m.

[0013] The luminous powder is a kind of light-storing and luminescent material known in the art, and can be strontium aluminate, lithium aluminum phosphate, strontium phosphate, zinc sulfide, etc. The luminous powder used in the specific embodiment of the present invention is strontium aluminate. The luminous powder is added to the topcoat layer to play the role of luminescence and supporting the coating. The energy storage size of each unit of luminous powder is constant. If the initial afterglow brightness is to be enhanced, the amount of luminous powder used needs to be increased; but using too much luminous powder will lead to a decrease in the mechanical properties of the topcoat layer. Therefore, the amount of luminous powder added to the topcoat layer is particularly important. The mass concentration of the luminous powder added in the technical solution of the present invention is at least 18wt%. If it is too little, the agglomeration tendency of the luminous powder itself in the conventional process preparation process is not large, but the improvement of the initial afterglow brightness and afterglow time is limited by the mass concentration of the luminous powder added; at most 25wt%, when the maximum amount of luminous powder added exceeds the above-defined maximum amount, even if the minimum viscosity of the topcoat layer is at the level of the above-defined minimum viscosity, it is difficult to avoid the agglomeration problem of the luminous powder, which leads to a low mechanical strength of the topcoat layer.

[0014] Usually, the dynamic viscosity of the polyurethane resin matrix used in the topcoat layer is at least 3000cps to ensure basic processing performance. In the technical solution of the present invention, the mass ratio of polyurethane resin to dispersing solvent is 1:4.3-7.7. When the amount of dispersing solvent is too much, it will affect the viscosity of the system, which will affect the overall production and processing quality of the veneer, and even make it impossible to process; when the amount of dispersing solvent added is too little, it is difficult to play a role in uniform dispersion.

[0015] Agent A and agent B in the dispersant are mutually soluble mixed solvents, and the luminous powder has different surface tension values ​​in agent A and agent B. The inventors found that when solvents with different surface tension values ​​are used, the aggregation ability of the luminous powder in the high-viscosity topcoat layer will be changed. This is because the surface tension will affect the aggregation ability of the luminous powder. When the luminous powder is dispersed in solvents with different surface tensions, the agglomeration resistance of the luminous powder can be increased, and the initial uniform dispersion state of the luminous powder can be stably maintained. However, when the absolute value of the difference between F1 and F2 is too small, the synergistic effect is not obvious; when the absolute value of the difference between F1 and F2 is too large, the difference in the drying speed gradient is too large, which is still not conducive to dispersion stability and leads to agglomeration problems.

[0016] As the preferred technical solution:

[0017] As described above, in the luminous topcoat slurry for dry veneer of microfiber leather for shoes, the mass ratio of agent A to agent B in the mixed solvent is 1:2 to 2:1. When the difference in the amount of agent A and agent B is too large, the dispersion stability of the luminous powder in the later construction process cannot be improved.

[0018] In the above-mentioned luminous topcoat slurry for dry veneer of microfiber leather for shoes, the mesh number of the luminous powder is 300 to 800. The mesh number of the luminous powder will also affect the agglomeration of the luminous powder. The higher the mesh number of the luminous powder, the finer the particle size, the greater the agglomeration tendency, and the agglomeration problem is difficult to avoid; the lower the mesh number of the luminous powder, the higher the particle size, which also affects the strength of the material.

[0019] The luminous topcoat slurry for dry veneer of microfiber leather for shoes as described above, wherein the agent A is DMF, and the agent B is diacetyl or xylene.

[0020] The present invention also provides a microfiber leather for shoes, comprising a base fabric layer, an adhesive layer and a luminous topcoat layer stacked in sequence, wherein the luminous topcoat layer is prepared by dry veneering using the luminous topcoat layer slurry as described in any of the above items.

[0021] As the preferred technical solution:

[0022] The microfiber leather for shoes as described above also includes a surface layer, which is located on the surface of the microfiber leather for shoes. The surface layer contains non-yellowing polyurethane resin. Since the luminous topcoat slurry contains inorganic powder, it will be rough if used directly as the surface layer, and it is necessary to design a surface layer material. In addition, when the surface layer is subjected to internal and external light radiation for a long time, its optical performance will be reduced, thereby affecting the luminous effect. Therefore, the resin in the surface layer is selected from non-yellowing polyurethane resin with high color change grade and good light transmittance.

[0023] As described above, the thickness ratio of the surface layer to the luminous topcoat layer is 1:6-15. If the thickness of the surface layer is too large, it will affect the light storage capacity and luminous capacity of the luminous topcoat layer, which is manifested in insufficient initial afterglow brightness and decreased afterglow time; if the thickness is too small, the roughness of the surface of the luminous topcoat layer cannot be improved.

[0024] The present invention also provides a method for preparing the microfiber leather for shoes as described in any one of the above items, comprising the following steps:

[0025] (1) Prepare microfiber base fabric material, adhesive layer slurry and luminous topcoat layer slurry;

[0026] (2) passing the release paper through a No. 1 coating roller, coating the surface of the release paper with a luminous topcoat slurry, and then drying and curing the luminous topcoat layer to form a luminous topcoat layer;

[0027] (3) coating the surface of the luminous topcoat layer in step (2) with a bonding layer slurry by means of a No. 2 coating roller, and combining the microfiber-based fabric material on the bonding layer slurry, followed by cross-linking, drying and curing, and separating the release paper to obtain the microfiber leather for shoes.

[0028] As the preferred technical solution:

[0029] In the method for preparing the microfiber leather for shoes as described above, the coating amount of the luminous topcoat slurry is 150-200 g / m 2 , in order to meet the initial afterglow brightness required, when the surface coating amount is too large, the thickness of the entire surface layer will be too large, and the thickness of the relatively microfiber base cloth will be insufficient, which cannot meet the performance of synthetic leather.

[0030] The coating amount of the adhesive layer slurry is set adaptively to enable the microfiber base fabric material and the luminous topcoat slurry to at least meet effective bonding or customer needs, for example, it is set to 10-50g / m 2 .

[0031] The method for preparing the microfiber leather for shoes as described above further comprises the step of coating the surface layer slurry on the release paper before coating the luminous topcoat slurry;

[0032] The coating amount of the surface slurry is 10 to 30 g / m 2 If it is too thin, the ideal surface cannot be obtained; if it is too thick, the light storage and luminous properties of the luminous topcoat layer will be affected;

[0033] The surface layer slurry comprises a non-yellowing polyurethane resin and a solvent, and the non-yellowing polyurethane resin has a discoloration grade of 5.

[0034] Beneficial effects:

[0035] (1) The present invention can make the topcoat layer have an ideal initial afterglow brightness and afterglow time by controlling the content of the luminous powder, and can also avoid the decrease of the mechanical properties of the topcoat layer.

[0036] (2) The present invention increases the agglomeration resistance of the luminous powder by selecting the solvent and ratio in the dispersant, and the initial uniform dispersion state of the luminous powder can be stably maintained, thereby avoiding the agglomeration problem of the luminous powder, making the obtained microfiber leather have a higher initial afterglow brightness and afterglow time, and also avoiding the problem of its poor mechanical strength.

[0037] (3) The present invention uses a non-yellowing polyurethane resin to minimize the effect of light transmittance on the surface layer even when it is exposed to internal and external light radiation for a long time, thereby improving the long-term light storage performance of the obtained microfiber leather for shoes. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0040] Initial afterglow brightness and afterglow time: The microfiber leather for shoes prepared in each embodiment and each comparative example was used as a sample, and a sample with a diameter of 5 cm was cut. Then, the afterglow brightness per minute was measured by a brightness meter using the luminous afterglow performance test method (the manufacturer of the equipment used was Zhejiang Multispectral Detection Technology Co., Ltd., model number was SSP9511). The afterglow brightness obtained by the equipment for the first time was recorded as the initial afterglow brightness. The initial afterglow brightness was reduced to 0.1 cd / m 2 The time when the light is on is recorded as the afterglow time, and the test conditions are: the excitation illumination is 1000 lux, the excitation time is 20 minutes, and the waiting time is 10 seconds.

[0041] Tensile strength of the luminous topcoat layer: The luminous topcoat layer slurry prepared in each embodiment and each comparative example was coated on a peeling panel into a film with a thickness of 0.5 mm using a scraper, and then cut into samples with a specification of 15 cm×2.54 cm. The tensile strength of the samples was then measured with reference to GB / T 1040.3-2006 standard. The manufacturer of the test equipment was Stema (Shanghai) Industrial Co., Ltd., the model was S2 series, and the test environment temperature was 25°C.

[0042] Dynamic viscosity: The polyurethane slurry prepared in each embodiment and each comparative example was used as a sample, and the dynamic viscosity of the sample was measured with reference to GB / T 2794-2013 standard. The manufacturer of the test equipment was Shanghai Sunny Hengping Scientific Instrument Co., Ltd., the model was NDJ-8S viscometer, the test temperature was 23°C, and the 3# rotor equipped with the viscometer was used.

[0043] Discoloration grade: The polyurethane resin in the surface slurry of each embodiment and each comparative example is used as a sample, and 10 parts of white powder (manufacturer is Fujian Huapu New Materials Co., Ltd., model number is 8906) are added to the sample by weight and mixed evenly to obtain slurry A, and then slurry A is applied on the peeling panel with a thickness of 0.5 mm using a scraper. After film formation, the film is placed on a yellowing resistance tester (manufacturer is High Speed ​​Rail Detection Instrument (Dongguan) Co., Ltd., model number is G1-7035-UB), and after irradiation with a 15W ultraviolet lamp for 4 hours, the sample color before and after ultraviolet lamp irradiation is compared with a gray card ratio, and rated according to GB / T251-2008 standard.

[0044] Example 1

[0045] A method for preparing microfiber leather for shoes, comprising the following steps:

[0046] (1) Raw material preparation;

[0047] Microfiber base fabric material: Microfiber single fabric, the manufacturer is Shanghai Huafeng Microfiber Technology Co., Ltd., the product number is DHKCO-120Y08, the thickness is 1.2mm, the color is black;

[0048] Adhesive layer slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDA-3530D;

[0049] Polyurethane slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDS-80Y, the solvent is DMF, and the solid content is 30%;

[0050] Agent A: DMF;

[0051] Agent B: xylene;

[0052] Luminous powder: strontium aluminate, mesh size 400;

[0053] Surface slurry: non-yellowing polyurethane resin slurry, the manufacturer is Huide Technology Co., Ltd., the brand is HDS-110Y, and the discoloration level is level 5;

[0054] (2) preparing luminous topcoat slurry;

[0055] First, a polyurethane slurry and a dispersing solvent (composed of an agent A and an agent B in a mass ratio of 1:1.6) are uniformly mixed to obtain a slurry with a dynamic viscosity of 3500 cps, and then a luminous powder is added thereto and mixed uniformly to obtain a luminous topcoat layer slurry; wherein the content of the luminous powder in the luminous topcoat layer slurry is 18wt%, the mass ratio of the polyurethane resin to the dispersing solvent is 1:6.3, the surface tension of the luminous powder in the agent A is recorded as F1, the surface tension of the luminous powder in the agent B is recorded as F2, and the absolute value of the difference between F1 and F2 is 5.8mN / m;

[0056] (3) firstly coating the surface slurry on the release paper, then coating the luminous topcoat slurry obtained in step (2) on the surface of the surface layer through a No. 1 coating roller, and finally drying at 125° C. for 10 min to solidify to form a composite layer; wherein the coating amount of the surface slurry is 15 g / m 2 The scraping amount of the luminous topcoat slurry is 150g / m 2 ;

[0057] (4) coating the surface of the composite layer in step (3) with a bonding layer slurry by a No. 2 coating roller, and combining the microfiber base cloth material on the bonding layer slurry, and then cross-linking and drying at 125° C. for 10 min to solidify, and then separating the release paper to obtain microfiber leather for shoes; wherein the coating amount of the bonding layer slurry is 50 g / m 2 .

[0058] The thickness ratio of the surface layer to the luminous topcoat layer of the finally prepared microfiber leather for shoes is 1:10, and the tensile strength of the luminous topcoat layer is 15.2MPa; the initial afterglow brightness of the microfiber leather for shoes is 1cd / m 2 The afterglow time is 152 minutes. The initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W UV lamp for 4 hours is 0.8cd / m 2 , the afterglow time is 134 minutes.

[0059] Comparative Example 1

[0060] A method for preparing microfiber leather for shoes is basically the same as that in Example 1, except that: the dispersing agent B in the luminous topcoat slurry is replaced by an agent A of equal mass; and the luminous topcoat slurry prepared in the comparative example is used in step (2).

[0061] The tensile strength of the luminous topcoat layer in the final microfiber leather for shoes is 10MPa; the initial afterglow brightness of the microfiber leather for shoes is 0.8cd / m 2 The afterglow time is 127 minutes; the initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W ultraviolet lamp for 4 hours is 0.5cd / m 2 , the afterglow time is 124 minutes.

[0062] By comparing Comparative Example 1 with Example 1, it can be seen that the tensile strength of the luminous topcoat layer in the microfiber leather for shoes prepared in Comparative Example 1 is significantly reduced, and the initial afterglow brightness and afterglow time are reduced. This is because the solvent of the luminous topcoat layer slurry of Comparative Example 1 is only DMF, and DMF cannot avoid the problem of luminous powder agglomeration, which will cause the agglomeration resistance of the luminous powder to become smaller when the luminous powder is dispersed in the solvent, thereby causing the agglomeration problem, which reduces the tensile strength of the luminous topcoat layer in the microfiber leather for shoes. In addition, the agglomeration of the luminous powder will also cause the powder particles to cover each other, affecting the reduction of light energy absorbed by the luminous powder, and ultimately reducing the initial afterglow brightness and afterglow time of the microfiber leather for shoes.

[0063] Comparative Example 2

[0064] A method for preparing microfiber leather for shoes is basically the same as that in Example 1, except that: the agent B used in the luminous topcoat slurry is cyclohexanol, the absolute value of the difference between F1 and F2 is 0.8 mN / m; and the luminous topcoat slurry prepared in the comparative example is used in step (2).

[0065] The tensile strength of the luminous topcoat layer in the final microfiber leather for shoes is 10.6MPa; the initial afterglow brightness of the microfiber leather for shoes is 0.9cd / m 2 The afterglow time is 139 minutes; the initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W ultraviolet lamp for 4 hours is 0.8cd / m 2 , the afterglow time is 130min.

[0066] By comparing Comparative Example 2 with Example 1, it can be seen that the tensile strength of the luminous topcoat layer in the microfiber leather for shoes prepared in Comparative Example 2 is reduced, and the initial afterglow brightness and afterglow time of the microfiber leather for shoes are reduced. This is because when the absolute value of the difference between F1 and F2 is too small, the synergistic effect is not obvious, and the agglomeration resistance of the luminous powder becomes smaller, which leads to an agglomeration problem, which reduces the tensile strength of the luminous topcoat layer in the microfiber leather for shoes, and because the luminous powder agglomerates in the solvent, the powder particles cover each other, which reduces the light energy absorbed by the luminous powder, and ultimately leads to a reduction in the initial afterglow brightness and afterglow time.

[0067] Comparative Example 3

[0068] A method for preparing microfiber leather for shoes is basically the same as that in Example 1, except that: the agent B used in the luminous topcoat slurry is isopropyl alcohol, the absolute value of the difference between F1 and F2 is 13.5 mN / m; and the luminous topcoat slurry prepared in the comparative example is used in step (2).

[0069] The tensile strength of the luminous topcoat layer in the final microfiber leather for shoes is 10.9MPa; the initial afterglow brightness of the microfiber leather for shoes is 0.9cd / m 2The afterglow time is 140 minutes. The initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W UV lamp for 4 hours is 0.8cd / m 2 , the afterglow time is 131 minutes.

[0070] By comparing Comparative Example 3 with Example 1, it can be seen that the tensile strength of the luminous topcoat layer in the microfiber leather for shoes prepared in Comparative Example 3 is reduced, and the initial afterglow brightness and afterglow time of the microfiber leather for shoes are reduced. This is because when the absolute value of the difference between F1 and F2 is too large, the difference in the drying speed gradients of different solvents is too large, which is still not conducive to dispersion stability, resulting in agglomeration problems, which reduces the tensile strength of the luminous topcoat layer in the microfiber leather for shoes, and because the luminous powder agglomerates in the solvent, the powder particles cover each other, which affects the reduction of light energy absorbed by the luminous powder, and ultimately leads to a reduction in the initial afterglow brightness and afterglow time.

[0071] Comparative Example 4

[0072] A method for preparing microfiber leather for shoes is basically the same as Example 1, except that: the manufacturer of the surface layer slurry in step (1) is Huide Technology Co., Ltd., the brand is HDS-80, and the color change level is 3.5; the surface layer slurry prepared in this comparative example is used in step (3).

[0073] The final microfiber leather for shoes has an initial afterglow brightness of 0.4 cd / m after being irradiated by a 15W UV lamp for 4 hours. 2 , the afterglow time is 30min.

[0074] By comparing Comparative Example 4 with Example 1, it can be seen that the long-term light storage performance of the microfiber leather for shoes prepared in Comparative Example 4 becomes poor. This is because the non-yellowing polyurethane resin used in Example 1 has a high color change level and good light transmittance. The microfiber leather for shoes prepared with it as the surface layer has little effect on light transmittance even when subjected to internal and external light radiation for a long time, thereby reducing the impact on the long-term light storage performance.

[0075] Example 2

[0076] A method for preparing microfiber leather for shoes, comprising the following steps:

[0077] (1) Raw material preparation;

[0078] Microfiber base fabric material: Microfiber single fabric, the manufacturer is Shanghai Huafeng Microfiber Technology Co., Ltd., the product number is DHKCO-120Y08, the thickness is 1.2mm, the color is black;

[0079] Adhesive layer slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDA-3530D;

[0080] Polyurethane slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDS-80Y, the solvent is DMF, and the solid content is 30%;

[0081] Agent A: DMF;

[0082] Agent B: diacetyl;

[0083] Luminous powder: strontium aluminate, mesh number is 300 mesh;

[0084] Surface slurry: non-yellowing polyurethane resin, manufactured by Huide Technology Co., Ltd., brand name HDS-130Y, discoloration level 5;

[0085] (2) preparing luminous topcoat slurry;

[0086] First, a polyurethane slurry and a dispersing solvent (composed of an agent A and an agent B in a mass ratio of 1.2:1) are uniformly mixed to obtain a slurry with a dynamic viscosity of 15000 cps, and then a luminous powder is added thereto and mixed uniformly to obtain a luminous topcoat layer slurry; wherein the content of the luminous powder in the luminous topcoat layer slurry is 20wt%, the mass ratio of the polyurethane resin to the dispersing solvent is 1:4.3, the surface tension of the luminous powder in the agent A is recorded as F1, the surface tension of the luminous powder in the agent B is recorded as F2, and the absolute value of the difference between F1 and F2 is 3.4mN / m;

[0087] (3) firstly coating the surface slurry on the release paper, then coating the luminous topcoat slurry obtained in step (2) on the surface of the surface through a No. 1 coating roller, and finally drying at 125° C. for 10 min to solidify to form a composite layer; wherein the coating amount of the surface slurry is 20 g / m 2 The scraping amount of the luminous topcoat slurry is 200g / m 2 ;

[0088] (4) coating the surface of the composite layer in step (3) with a bonding layer slurry by a No. 2 coating roller, and combining the microfiber base cloth material on the bonding layer slurry, and then cross-linking and drying at 125° C. for 10 min to solidify, and then separating the release paper to obtain microfiber leather for shoes; wherein the coating amount of the bonding layer slurry is 50 g / m 2 .

[0089] The thickness ratio of the surface layer to the luminous topcoat layer of the finally prepared microfiber leather for shoes is 1:10, and the tensile strength of the luminous topcoat layer is 14.3MPa; the initial afterglow brightness of the microfiber leather for shoes is 1.6cd / m 2 The afterglow time is 202 minutes. The initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W UV lamp for 4 hours is 1.2cd / m 2 , the afterglow time is 179 minutes.

[0090] Example 3

[0091] A method for preparing microfiber leather for shoes, comprising the following steps:

[0092] (1) Raw material preparation;

[0093] Microfiber base fabric material: Microfiber single fabric, the manufacturer is Shanghai Huafeng Microfiber Technology Co., Ltd., the product number is DHKCO-120Y08, the thickness is 1.2mm, the color is black;

[0094] Adhesive layer slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDA-3530D;

[0095] Polyurethane slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDS-80Y, the solvent is DMF, and the solid content is 30%;

[0096] Agent A: DMF;

[0097] Agent B: diacetyl;

[0098] Luminous powder: strontium aluminate, mesh number is 800 mesh;

[0099] Surface slurry: non-yellowing polyurethane resin, manufactured by Huide Technology Co., Ltd., brand name HDS-130Y, discoloration level 5;

[0100] (2) preparing luminous topcoat slurry;

[0101] First, a polyurethane slurry and a dispersing solvent (composed of an agent A and an agent B in a mass ratio of 1:1) are uniformly mixed to obtain a slurry with a dynamic viscosity of 13000 cps, and then a luminous powder is added thereto and mixed uniformly to obtain a luminous topcoat layer slurry; wherein the content of the luminous powder in the luminous topcoat layer slurry is 22wt%, the mass ratio of the polyurethane resin to the dispersing solvent is 1:4.7, the surface tension of the luminous powder in the agent A is recorded as F1, the surface tension of the luminous powder in the agent B is recorded as F2, and the absolute value of the difference between F1 and F2 is 3.4mN / m;

[0102] (3) firstly coating the surface slurry on the release paper, then coating the luminous topcoat slurry obtained in step (2) on the surface of the surface layer through a No. 1 coating roller, and finally drying at 125° C. for 10 min to solidify to form a composite layer; wherein the coating amount of the surface slurry is 10 g / m 2 The scraping amount of the luminous topcoat slurry is 150g / m 2 ;

[0103] (4) coating the surface of the composite layer in step (3) with a bonding layer slurry by a No. 2 coating roller, and combining the microfiber base cloth material on the bonding layer slurry, and then cross-linking and drying at 125° C. for 10 min to solidify, and then separating the release paper to obtain microfiber leather for shoes; wherein the coating amount of the bonding layer slurry is 50 g / m 2 .

[0104] The thickness ratio of the surface layer to the luminous topcoat layer of the finally prepared microfiber leather for shoes is 1:14, and the tensile strength of the luminous topcoat layer is 16MPa; the initial afterglow brightness of the microfiber leather for shoes is 1.2cd / m 2 The afterglow time is 174 minutes; the initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W ultraviolet lamp for 4 hours is 1cd / m 2 , the afterglow time is 155min.

[0105] Example 4

[0106] A method for preparing microfiber leather for shoes, comprising the following steps:

[0107] (1) Raw material preparation;

[0108] Microfiber base fabric material: Microfiber single fabric, the manufacturer is Shanghai Huafeng Microfiber Technology Co., Ltd., the product number is DHKCO-120Y08, the thickness is 1.2mm, the color is black;

[0109] Adhesive layer slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDA-3530D;

[0110] Polyurethane slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDS-80Y, the solvent is DMF, and the solid content is 30%;

[0111] Agent A: DMF;

[0112] Agent B: xylene;

[0113] Luminous powder: strontium aluminate, mesh number is 600 mesh;

[0114] Surface slurry: non-yellowing polyurethane resin, manufactured by Huide Technology Co., Ltd., brand name HDS-130Y, discoloration level 5;

[0115] (2) preparing luminous topcoat slurry;

[0116] First, a polyurethane slurry and a dispersing solvent (composed of an agent A and an agent B in a mass ratio of 1:2) are uniformly mixed to obtain a slurry with a dynamic viscosity of 3000 cps, and then a luminous powder is added thereto and mixed uniformly to obtain a luminous topcoat layer slurry; wherein the content of the luminous powder in the luminous topcoat layer slurry is 25wt%, the mass ratio of the polyurethane resin to the dispersing solvent is 1:7.7, the surface tension of the luminous powder in the agent A is recorded as F1, the surface tension of the luminous powder in the agent B is recorded as F2, and the absolute value of the difference between F1 and F2 is 5.8mN / m;

[0117] (3) firstly coating the surface slurry on the release paper, then coating the luminous topcoat slurry obtained in step (2) on the surface of the surface layer through a No. 1 coating roller, and finally drying at 125° C. for 10 min to solidify to form a composite layer; wherein the coating amount of the surface slurry is 10 g / m 2 The scraping amount of the luminous topcoat slurry is 160g / m 2 ;

[0118] (4) coating the surface of the composite layer in step (3) with a bonding layer slurry by a No. 2 coating roller, and combining the microfiber base cloth material on the bonding layer slurry, and then cross-linking and drying at 125° C. for 10 min to solidify, and then separating the release paper to obtain microfiber leather for shoes; wherein the coating amount of the bonding layer slurry is 50 g / m 2 .

[0119] The thickness ratio of the surface layer to the luminous topcoat layer of the finally prepared microfiber leather for shoes is 1:15, and the tensile strength of the luminous topcoat layer is 15MPa; the initial afterglow brightness of the microfiber leather for shoes is 1.6cd / m 2 The afterglow time is 207 minutes. The initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W UV lamp for 4 hours is 1.2cd / m 2 , the afterglow time is 178 minutes.

[0120] Example 5

[0121] A method for preparing microfiber leather for shoes, comprising the following steps:

[0122] (1) Raw material preparation;

[0123] Microfiber base fabric material: Microfiber single fabric, the manufacturer is Shanghai Huafeng Microfiber Technology Co., Ltd., the product number is DHKCO-120Y08, the thickness is 1.2mm, the color is black;

[0124] Adhesive layer slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDA-3530D;

[0125] Polyurethane slurry: The manufacturer is Huide Technology Co., Ltd., the brand is HDS-80Y, the solvent is DMF, and the solid content is 30%;

[0126] Agent A: DMF;

[0127] Agent B: diacetyl;

[0128] Luminous powder: strontium aluminate, mesh number is 500 mesh;

[0129] Surface slurry: non-yellowing polyurethane resin, manufactured by Huide Technology Co., Ltd., brand name HDS-110Y, discoloration level 5;

[0130] (2) preparing luminous topcoat slurry;

[0131] First, a polyurethane slurry and a dispersing solvent (composed of an agent A and an agent B in a mass ratio of 2:1) are uniformly mixed to obtain a slurry with a dynamic viscosity of 4000 cps, and then a luminous powder is added thereto and mixed uniformly to obtain a luminous topcoat layer slurry; wherein the content of the luminous powder in the luminous topcoat layer slurry is 25wt%, the mass ratio of the polyurethane resin to the dispersing solvent is 1:5.7, the surface tension of the luminous powder in the agent A is recorded as F1, the surface tension of the luminous powder in the agent B is recorded as F2, and the absolute value of the difference between F1 and F2 is 3.4mN / m;

[0132] (3) firstly coating the surface slurry on the release paper, then coating the luminous topcoat slurry obtained in step (2) on the surface of the surface layer through a No. 1 coating roller, and finally drying at 125° C. for 10 min to solidify to form a composite layer; wherein the coating amount of the surface slurry is 30 g / m 2 The scraping amount of the luminous topcoat slurry is 200g / m 2 ;

[0133] (4) coating the surface of the composite layer in step (3) with a bonding layer slurry by a No. 2 coating roller, and combining the microfiber base cloth material on the bonding layer slurry, and then cross-linking and drying at 125° C. for 10 min to solidify, and then separating the release paper to obtain microfiber leather for shoes; wherein the coating amount of the bonding layer slurry is 50 g / m 2 .

[0134] The thickness ratio of the surface layer to the luminous topcoat layer of the finally prepared microfiber leather for shoes is 1:6, and the tensile strength of the luminous topcoat layer is 14.5MPa; the initial afterglow brightness of the microfiber leather for shoes is 1.7cd / m 2 The afterglow time is 217 minutes; the initial afterglow brightness of the microfiber leather for shoes after being irradiated by a 15W ultraviolet lamp for 4 hours is 1.3cd / m 2 , the afterglow time is 186 minutes.

Claims

1. A luminous topcoat slurry for dry-process veneer of microfiber leather for shoes, the base material of which is polyurethane slurry, characterized in that: 18-25wt% of luminous powder is dispersed in the base material; The polyurethane slurry comprises a polyurethane resin and a dispersion-promoting solvent, the mass ratio of the polyurethane resin to the dispersion-promoting solvent is 1:4.3-7.7, and the dynamic viscosity of the polyurethane slurry is 3000-15000 cps; The dispersibility-promoting solvent is a mixed solvent of agent A and agent B, and the agent A and the agent B are mutually soluble; The surface tension of the luminous powder in the agent A is recorded as F1, and the surface tension of the luminous powder in the agent B is recorded as F2. The absolute value of the difference between F1 and F2 is 3 to 6 mN / m.

2. The luminous topcoat slurry for dry veneer of microfiber leather for shoes according to claim 1, characterized in that: The mass ratio of agent A to agent B in the mixed solvent is 1:2 to 2:

1.

3. The luminous topcoat slurry for dry veneer of microfiber leather for shoes according to claim 1, characterized in that: The mesh number of the luminous powder is 300 to 800 meshes.

4. The luminous topcoat slurry for dry veneer of microfiber leather for shoes according to claim 1, characterized in that: The agent A is DMF, and the agent B is diacetyl or xylene.

5. A microfiber leather for shoes, comprising a base fabric layer, an adhesive layer and a luminous topcoat layer stacked in sequence, characterized in that: The luminous topcoat layer is prepared by dry veneering using the luminous topcoat layer slurry as described in any one of claims 1 to 4.

6. The microfiber leather for shoes according to claim 5, characterized in that: It also includes a surface layer, which is located on the surface layer of the microfiber leather for shoes and contains a non-yellowing polyurethane resin.

7. The microfiber leather for shoes according to claim 6, characterized in that: The thickness ratio of the surface layer to the luminous topcoat layer is 1:6-15.

8. The method for preparing the microfiber leather for shoes according to any one of claims 5 to 7, characterized in that The steps include: (1) Prepare microfiber base fabric material, adhesive layer slurry and luminous topcoat layer slurry; (2) passing the release paper through a No. 1 coating roller, coating the surface of the release paper with a luminous topcoat slurry, and then drying and curing the luminous topcoat layer to form a luminous topcoat layer; (3) coating the surface of the luminous topcoat layer in step (2) with a bonding layer slurry by means of a No. 2 coating roller, and combining the microfiber-based fabric material on the bonding layer slurry, followed by cross-linking, drying and curing, and separating the release paper to obtain the microfiber leather for shoes.

9. The method for preparing microfiber leather for shoes according to claim 8, characterized in that: The coating amount of the luminous topcoat slurry is 150-200 g / m 2 .

10. The method for preparing microfiber leather for shoes according to claim 8, characterized in that: The method also includes the step of coating the surface layer slurry on the release paper before coating the luminous topcoat layer slurry; The coating amount of the surface slurry is 10 to 30 g / m 2 ; The surface layer slurry comprises a non-yellowing polyurethane resin and a solvent, and the non-yellowing polyurethane resin has a discoloration grade of 5.